已知y=cosx,则y[sup](10)[/]=( ). A: cosx B: -cosx C: sinx D: -sinx
已知y=cosx,则y[sup](10)[/]=( ). A: cosx B: -cosx C: sinx D: -sinx
sinx-(1/cosx),以及sinx+(1/cosx)的最值
sinx-(1/cosx),以及sinx+(1/cosx)的最值
已知y=cosx,则y[sup](10)[/]=( ). A: sinx: B: cosx: C: -sinx; D: -cosx.
已知y=cosx,则y[sup](10)[/]=( ). A: sinx: B: cosx: C: -sinx; D: -cosx.
-∫d(cosx)/(2+cosx)(1+cosx)(1-cosx)=∫[1/3(2+cosx)-1/2(1+cosx)-1/6(1-cosx)]dcosx中的326怎么配的
-∫d(cosx)/(2+cosx)(1+cosx)(1-cosx)=∫[1/3(2+cosx)-1/2(1+cosx)-1/6(1-cosx)]dcosx中的326怎么配的
(lnsinx)’=1/cosx
(lnsinx)’=1/cosx
1的x方小于cosx
1的x方小于cosx
1的x方小于cosx。
1的x方小于cosx。
y=x^cosx,则y'(1)=
y=x^cosx,则y'(1)=
(xsinx)′=x′ · (sinx)′=1 · cosx=cosx.
(xsinx)′=x′ · (sinx)′=1 · cosx=cosx.
f(x)=根号[(sinx)四次方+4(cosx)四次方]-根号【(cosx)四次方+4(sinx)四次方】,求f(pi/8)
f(x)=根号[(sinx)四次方+4(cosx)四次方]-根号【(cosx)四次方+4(sinx)四次方】,求f(pi/8)